Interaction of centrosomal component SPD-5 with Wnt signals in the control of cell polarity in Caenorhabditis elegans - Han, Suhao (Kansas State University, 2012)
All multicellular organisms consist of a variety of cell types. One of the mechanisms to generate this cellular diversity is the asymmetric cell division, which requires the establishment of cell polarity. In Caenorhabditis elegans hermaphrodites, 807 of 949 somatic cell divisions are asymmetric. The centrosome and the Wnt signaling pathway both have been shown to regulate cell polarity and subsequently asymmetric divisions in many model organisms. However, it is not clear whether the Wnt signaling pathway manipulates the cell polarity through specific cellular organelles, such as the centrosome. To address this question, we examined a centrosomal component, SPD-5, to see whether it cooperates with the Wnt signaling pathway to regulate certain asymmetric cell divisions. We showed that SPD-5, which was originally found to be critical for the embryonic development, also played a role during certain post-embryonic cell divisions in C. elegans. Specifically the asymmetric divisions of seam cells that required SPD-5 function were also known to be regulated by the Wnt signaling pathway. Thus the stem-cell like seam cell divisions could be an intriguing system to study the interaction of centrosomes and the Wnt pathway. We found that SPD-5 was required for a successful cell division, similar to other centrosomal components. This suggests that SPD-5 still functions as a centrosomal component during C. elegans post-embryonic development. It has been shown that establishment of seam cell polarity relies on the asymmetric localization of certain Wnt pathway components. Interestingly, we found that SPD-5 was required for the proper localization of several Wnt components in a way that was independent of a key MTOC (microtubule-organizing center) member γ-tubulin. In addition, SPD-5 genetically interacted with the Wnt pathway components APR-1/APC and POP-1/Tcf to regulate asymmetric divisions of seam cells. These data suggest that SPD-5 interacts with the Wnt signaling pathway in controlling the polarity of seam cells. Overall, our results suggest a novel role of SPD-5 in cooperating with the Wnt signaling pathway to regulate cell polarity and asymmetric cell division, in addition to its function as a centrosomal component.
Keywords: Asymmetric cell division; Cell polarity; Centrosome; Wnt pathway; Biology (0306); Molecular Biology (0307)